MODERN ART SALONS AS CREATIVE ECONOMIC INSTITUTIONS: BUSINESS MODELS, DIGITAL TRANSFORMATION, AND CULTURAL SUSTAINABILITY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article analyzes the conceptual foundations of modern art salons and their role within the contemporary cultural and economic system. The research examines the transformation of art salons from traditional exhibition spaces into multifunctional creative-economic institutions integrating cultural communication, business activity, and digital technologies. Particular attention is devoted to business models, financial planning mechanisms, infrastructure management, and digital transformation processes in modern art salons. The study also evaluates the economic effectiveness of art salons through indicators such as investment attraction, employment generation, digital sales, and regional economic influence. The findings demonstrate that modern art salons function not only as cultural institutions but also as strategic drivers of creative industries, urban development, and cultural sustainability.